1α, 25-Dihydroxyvitamin D3 protects gastric mucosa epithelial cells against Helicobacter pylori-infected apoptosis through a vitamin D receptor-dependent c-Raf/MEK/ERK pathway. (31st December 2022) - Zhao, Shuai; Wan, Daihong; Zhong, Yaoyao; Xu, Xiwei
Abstract: Context: Due to the resistance of Helicobacter pylori to antibiotics, it is difficult to eradicate this pathogenic bacterium from the host. The role of 1α, 25-dihydroxyvitamin D3 (1, 25-D3) in H. pylori -infected gastric mucosa epithelial cells remains unknown. Objective: This study investigates the protective property of 1, 25-D3 against H. pylori -infected apoptosis in gastric mucosa epithelial cells and its potential molecular mechanisms. Materials and methods: GES-1 cells were infected with H. pylori SS1 strain (MOI: 100) and treated with 1, 25-D3 at 100, 200, and 300 nM for 24 h. Mice were orally gavaged with 10 8 CFUs of H. pylori and 25 µg/kg 1, 25-D3 every other day for 1 month. CCK-8, LDH assay, TUNEL assay and western blot were used to determine the effect of 1, 25-D3 on H. pylori -induced apoptosis. Results: H. pylori infection decreased cell viability to 59.2%, while 100–300 nM 1, 25-D3 increased cell viability to 62.2%, 78.4% and 87.1%, respectively. Compared with positive control (4.53-fold), 1, 25-D3 reduced caspase-3 activity to 4.49-, 2.88- and 1.49-fold, reduced caspase-6 activity to 2.36-, 1.88- and 1.50-fold, reduced caspase-9 activity to 4.55-, 2.91- and 2.01-fold. 1, 25-D3 alters Bcl-2 family, caspase protein expression and c-Raf/MEK/ERK phosphorylation levels in vivo and in vitro . Suppression of 1, 25-D3 in apoptosis was reliant on binding to vitamin D receptor. The pharmacological inhibition of c-Raf/MEK/ERK phosphorylation blocked the anti-apoptotic effect of 1, 25-D3. Discussion and conclusion: 1, 25-D3 protected gastric mucosa epithelial cells against H. pylori -infected apoptosis through a VDR-dependent c-Raf/MEK/ERK pathway.